Interaction of hypercaloric diet and physical exercise on lipid profile, oxidative stress and antioxidant defenses - Burneiko, Regina C. M.; Diniz, Yeda S.; Galhardi, Cristiano M.; Rodrigues, Hosana G.; Ebaid, Geovana M. X.; Faine, Luciane A.; Padovani, Carlos R.; Cicogna, Antonio C.; Novelli, Ethel L. B. (Elsevier B.V., 2006)
The present study examined the interaction of hypercaloric diet (HD) and physical exercise on lipid profile and oxidative stress in serum and liver of rats. Male Wistar rats (60-days-old) were fed with a control (C) and hypercaloric diet (H). Each of the two dietary groups (C and H) was divided into three subgroups (n = 8), sedentary (CS and HS), exercised 2 days a week (CE2 and HE2) and exercised 5 days a week (CE5 and HE5). The swimming was selected as a model for exercise performance. After 8-weeks exercised rats showed decreased lactate dehydrogenase serum activities, demonstrating the effectiveness of the swimming as an aerobic-training protocol. Exercise 5-days a week reduced the body weight gain. Triacylglycerol (TG) and very low-density lipoprotein (VLDL-C) were increased in HD-fed rats. HE5 and CE5 rats had decreased TG, VLDL-C and cholesterol. HE2 rats had enhanced high-density lipoprotein (HDL-C) in serum. No alterations were observed in lipid hydroperoxide (LH), while total antioxidant substances (TAS) were increased in serum of exercised rats. HD-fed rats had hepatic TG accumulation. Superoxide dismutase activities were increased and catalase was decreased in liver of exercised rats. The interaction of HD and physical exercise reduced TAS and enhanced LH levels in hepatic tissue. In conclusion, this study confirmed the beneficial effect of physical exercise as a dyslipidemic-lowering component. Interaction of HD and physical exercise had discrepant effects on serum and liver oxidative stress. The interaction of HID and physical exercise reduced the oxidative stress in serum. HD and physical exercise interaction had pro-oxidant effect on hepatic tissue, suggesting that more studies should be done before using physical exercise as an adjunct therapy to reduce the adverse effects of HD. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: hypercaloric diet; physical exercise; lipid profile; oxidative stress; serum; liver